ANALISIS KONFLIK PEMANFAATAN RUANG KAWASAN PESISIR DI DARAT DAN PERAIRAN KECAMATAN LABBAKKANG KABUPATEN PANGKEP - Hasriyanti; Suprapta; Dinil Qaiyimah (Universitas Negeri Makassar, 2023)
Coastal spatial planning is very important for solving spatial use conflicts, namely by identifying and mapping all the uses, regulations and conflicts that occur. The purpose of this study aims to evaluate the suitability of land use in coastal area spatial use, analyze the factors that cause spatial use conflicts in coastal area resource management, and determine land use priorities in the spatial utilization of coastal areas on land and water in Labakang District, Pangkep Regency. This research uses a mix method research type, namely a combination of quantitative and qualitative research. Data analysis techniques were performed using a Geographic Information System (GIS). To evaluate land suitability, a spatial analysis was carried out using a GIS approach using ArcInfo 3.5 and ArcView 3.1 software using overlay, weighting, scoring and class methods. This study found that spatial conflicts in the coastal area of Labakkang District occurred due to efforts to fulfill needs and control access to coastal natural resources, especially land. This situation causes spatial conflicts between interest groups in the utilization of coastal areas. This is caused by an increase in tourism activity in the coastal area of Labakang District, which was followed by an increase in the escalation of interest in it.